Tribal leadership leveraging natural groups to build a thriving organization - Logan, David; King, John Paul 1941-; Fischer-Wright, Halee (Harper Business, 2011)
Describes how corporate leaders can manage group dynamics to maximize productivity, in a guide based on an eight-year study of over two dozen companies that also draws on insights by NASCAR CEO Brian France and Dilbert creator Scott Adams